2008
DOI: 10.15809/irriga.2008v13n3p367-377
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência Do Uso Da Água E Nitrogênio Na Produção De Melão

Abstract: EFICIÊNCIA DO USO DA ÁGUA E NITROGÊNIO NA PRODUÇÃO DE MELÃO   Rodrigo Otávio Câmara Monteiro1; Raimundo Nonato Távora Costa2; Moisés Custódio Saraiva Leão2; José Vanglésio de Aguiar3[1]Centro Federal de Educação Tecnológica de Bento Gonçalves (CEFET-BG), Bento Gonçalves, RS, rodrigomonteiro@cefetbg.gov.br2Departamento de Engenharia Agrícola, Centro Ciências Agrárias, Universidade Federal Ceará, Fortaleza, CE3Instituto Brasileiro de Geografia e Estatística - IBGE.  1 RESUMO A intensificação dos cultivos e os as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
2
4
2
4
Order By: Relevance
“…These results disagree with those of Mo-rais et al (2008), who evaluated the response of watermelon plants at different water depths and nitrogen levels in the Curu Valley in Pentecoste, Ceará, Brazil, and found that different water depths and nitrogen doses affected WUE. However, the present results corroborate those of Monteiro et al (2008) for melon plants in the municipality of Pentecoste, Ceará, who found that the water depths, but not the nitrogen doses, significantly affected WUE. The maximum WUE (21.11 kg m -3 ) corresponds to the water depth 110.42 mm.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…These results disagree with those of Mo-rais et al (2008), who evaluated the response of watermelon plants at different water depths and nitrogen levels in the Curu Valley in Pentecoste, Ceará, Brazil, and found that different water depths and nitrogen doses affected WUE. However, the present results corroborate those of Monteiro et al (2008) for melon plants in the municipality of Pentecoste, Ceará, who found that the water depths, but not the nitrogen doses, significantly affected WUE. The maximum WUE (21.11 kg m -3 ) corresponds to the water depth 110.42 mm.…”
Section: Resultssupporting
confidence: 91%
“…The WUE values corroborate those found by Monteiro et al (2008), who evaluated WUE and NUE in melon crops in Pentecoste, Ceará, at the water depths of 232.7, 334.7, 422.1, and 567.8 mm and nitrogen doses of 0, 75, 150, and 300 kg ha -1 , and found that WUE decreased as the water depths increased but was not significantly affected by nitrogen. Moreover, WUE was highest using 232.7 mm of water.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations